Alteration in soil arsenic dynamics and toxicity to sunflower (Helianthus annuus L.) in response to phosphorus in different textured soils. (January 2022) - Piracha, Muhammad Awais; Ashraf, Muhammad; Shahzad, Sher Muhammad; Imtiaz, Muhammad; Arif, Muhammad Saleem; Rizwan, Muhammad Shahid; Aziz, Ahsan; Tu, Shuxin; Albasher, Gadah; Alkahtani, Saad; Shakoor, Awais
Abstract: Being analogue to arsenic (As), phosphorus (P) may affect As dynamics in soil and toxicity to plants depending upon many soil and plant factors. Two sets of experiments were conducted to determine the effect of P on As fractionation in soils, its accumulation by plants and subsequent impact on growth, yield and physiological characteristics of sunflower ( Helianthus annuus L.). Experimental plan comprised of two As levels (60 and 120 mg As kg −1 soil), four P (0-5-10-20 g phosphate rock kg −1 soil) and three textural types (sandy, loamy and clayey) with three replications. Among different As fractions determined, labile, calcium-bound, organic matter-bound and residual As increased while iron-bound and aluminum-bound As decreased with increasing P in all the three textural types. Labile-As percentage increased in the presence of P by 16.9–48.0% at As60 while 36.0–68.1% at As120 in sandy, 19.1–64.0% at As60 while 11.5–52.3% at As120 in loamy, and 21.8–58.2% at As60 while 22.3–70.0% at As120 in clayey soil compared to respective As treatment without P. Arsenic accumulation in plant tissues at both contamination levels declined with P addition as evidenced by lower bioconcentration factor. Phosphorus mitigated the As-induced oxidative stress expressed in term of reduced hydrogen peroxide, malondialdehyde while increased glutathione, and consequently improved the achene yield. Although, P increased As solubility in soil but restricted its translocation to plant, leading to reversal of oxidative damage, and improved sunflower growth and yield in all the three soil textural types, more profound effect at highest P level and in sandy texture. Graphical abstract: Image 1 Highlights: Arsenic can have serious repercussions both for human and animal health by compromising the soil, water and food quality. Phosphorus could alter As fractions in soils, an increase in L-As, Ca–As, OM-As and R–As while decrease in Fe–As and Al–As. Arsenic-induced oxidative stress in term of H2 O2 and MDA could efficiently be ameliorated with P in sunflower. Phosphorus could increase As solubility and mobility in soil, but restricted its accumulation in plant tissues. Ameliorative effects of P against As toxicity in sunflower were more profound at highest P level and in sandy texture. Abstract : P had a marked effect on As fractionation in all the three textured soils but the effect was highest at elevated P level, and in sandy soil. P-induced resistance to As toxicity was associated with an inhibition in As accumulation, and protection against oxidative stress by activating the antioxidant system.